(untitled) (Al-Qamar, 2023)
Though, Taʻqeed-e-lafzī is counted in the flaws of poetry, but it has caused creation of beauty in Ghalib’s poetry. Notwithstanding to mastery over poetic version and expression, great number of poetic norms are victims to Taʻqeed-e-lafzī. But this Taʻqeed-e-lafzī does not cause the ambiguity and complication in poetry just like other poets. This is an ample proof that Ghalib has contributed beautification to his poetry by dint of Taʻqeed-e-lafzī found in Ghalib’s poetry, Taʻqeed-e-lafzī is not given birth thanks to incapability and inexperience in communication. But Ghalib handles this artful tactic consciously. This tactic has been caused increase in the beautification of Ghalib’s poetry. Ghalib’s individuality is that despite Taʻqeed-e-lafzī, his poetry escapes from being difficult and ambiguous. If the reader may have a little bit familiarity with Ghalib’s poetry and creative disposition, it does not linger difficult to efface Taʻqeed-e-lafzī found in Ghalib’s poetry.